Application of embedded generation in distrubution system using Artificial Immune System (AIS) - Muhamad Tarmimi, Abu Bakar (Universiti Malaysia Perlis, 2008)
Every distribution system has losses that will reduce the performance of the system. Thus the distribution system can not distribute maximum power for consumer. However, distribution system engineers have preferred to choose techniques that can be used to reduce losses. The technique that can be used is artificial immune system that can perform to find and determine the suitable size of generator to use in distribution system. This is suitable with the objectives of the project that needs to reduce the losses and to obtain the suitable size of generator and the Newton Raphson method will be applied as power flow solution. This test system using 6-bus test system and use Matlab software to do the programming. The knowledge of Matlab software should be studied deeply to simplify the application of programming and mathematical calculation. Other than that, understanding about power flow solution using Newton Raphson method and artificial immune system technique should be considered deeply.